Zulfikarpašić-Milošević agreement in 1991. - Mr. Hamza MEMIŠEVIĆ (Historijski pogledi, 2023)
Historical Background and the Emergence of New Bibliographic Units in the Context of the Contemporary Political Moment Demand a Reevaluation of Previous Interpretations Related to Events in the Territory of the Former Socialist Yugoslavia. This paper focuses on the Historical Agreement, also known as the Zulfikarpašić-Milošević Agreement, initiated by Muslims (Bosniaks). The agreement was intended as a peace and political initiative but came late in the context of the war in Croatia and the policy of regionalization pursued by the Serbian side in Bosnia and Herzegovina. After leaving the Party of Democratic Action (SDA), Adil Zulfikarpašić founded the Muslim Bosniak Organization (MBO), with the support of academician Muhamed Filipović. Dissatisfied with the policies of the SDA, Zulfikarpašić and Filipović sought to address the crisis through a different approach. In the case of the MBO, this approach involved historical reconciliation with the Serbs. While the leaders of the MBO structured this agreement as a peace and political initiative, its implementation was not possible due to the opposing state-legal concepts from the Bosniak (Muslim) side. The concept of a union of free states, central to the MBO's agreement, did not receive support from the Serbian side. In such a constellation of relationships, Yugoslavia could continue to function only as a federal state, as it best served Serbian state interests. The fundamental aim of this work is to shed light on the events preceding the agreement, what the agreement entailed, and why it ultimately failed. The introductory section of the paper analyzes Muslim (Bosniak)-Serbian historical reconciliation, which includes the period of Austro-Hungarian rule and the Kingdom of Yugoslavia when certain Muslim (Bosniak) politicians formed a specific type of alliance with the Serbs. The position of Muslims (Bosniaks) in the early 1990s significantly differed from that at the beginning of the 20th century. The paper dedicates a substantial portion of its pages to significant events in the Second Yugoslavia to provide a comprehensive synthesis. The 1974 Constitution, the Memorandum of the Serbian Academy of Sciences and Arts (SANU), the rise of Milošević, the abolition of autonomy for provinces in Serbia, and the republic-level elections were all events that preceded the agreement. Special attention in the paper is given to the participants of the agreement as significant political protagonists of that period, as well as the political parties whose members were part of the agreement and the architects of the policies of that era. Adil beg Zulfikarpašić undeniably played a central role in the efforts to reach a historical agreement between Muslims (Bosniaks) and Serbs. After World War II, Zulfikarpašić went into exile, where he launched the Bosanski pogledi magazine in the early 1960s. During his time in exile, he operated from various political-ideological positions, later emerging as one of the ideologues of Bosniak identity. In 1963, Zulfikarpašić participated in the founding of the Democratic Alternative, a movement in which Bosniak, Croatian, Serbian, and Slovenian intellectuals advocated for the democratization of Yugoslavia and the concept of free states within Yugoslavia. The foundation of this movement was a departure from Yugoslavia, i.e., communism, and alignment with the Western bloc of countries that based their policies on the principles of capitalism and democracy. Zulfikarpašić remained unwaveringly convinced of the correctness of the political initiative for reconciliation with the Serbs, considering the agreement the best solution under the circumstances and the only alternative to the impending war. A. Zulfikarpašić, as the main architect of the agreement, left Bosnia and Herzegovina in September 1991, and shortly thereafter, his party colleague, academician Muhamed Filipović, terminated all processes related to the agreement.